Audit firms under pressure: turning the tide on auditor turnover - UiTM, MITASA (Kesatuan Kakitangan Akademik UiTM (MITASA), 2025)
The audit industry is unique, as the quality of the audit depends critically on the excellence of the audit team. Therefore, the most asset in audit firms is the auditors. The audit industry faces a critical challenge marked by a pervasive issue: a substantial and recurring turnover of employees. People have always perceived the audit profession as both challenging and highly stressful, particularly during peak seasons. This high rate of employee turnover poses significant concerns and demands attention to identify its root causes, understand its impact on the industry, and formulate effective strategies for retention.